An Investigation on the Audit Committees Effectiveness: The Case for GLCs in Malaysia - Jamil, Nurul Nazlia; Nelson, Sherliza Puat (Gadjah Mada International Journal of Business, 2011)
Financial reporting quality has been under scrutiny especially after the collapse of major companies. The main objective of this study is to investigate the audit committeeâs effectiveness on the financial reporting quality among the Malaysian GLCs following the transformation program. In particular, the study examined the impact of audit committee characteristics (independence, size, frequency of meeting and financial expertise) on earnings management in periods prior to and following the transformation program (2003-2009). As of 31 December 2010, there were 33 public-listed companies categorized as Government-Linked Companies (GLC Transformation Policy, 2010) and there were 20 firms that have complete data that resulted in the total number of firm-year observations to 120 for six years (years 2003-2009).Â  Results show that the magnitude of earnings management as proxy of financial reporting quality is influenced by the audit committee independence. Agency theory was applied to explain audit committee, as a monitoring mechanism as well as reducing agency costs via gaining competitive advantage in knowledge, skills, and expertise towards financial reporting quality. The study is important as it provides additional knowledge about the impact of audit committees effectiveness on reducing the earnings management, and assist practitioners, policymakers and regulators such as Malaysian Institute of Accountants, Securities Commission and government to determine ways to enhance audit committees effectiveness and improve the financial reporting of GLCs, as well as improving the quality of the accounting profession.Â Â Â Â Â